Shaping the Future of Perinatal Cells: Lessons From the Past and Interpretations of the Present - Silini, Antonietta R.; Masserdotti, Alice; Papait, Andrea; Parolini, Ornella (Frontiers in Bioengineering and Biotechnology, 2019)
Since their discovery and characterization, mesenchymal stromal cells (MSC) have been a topic of great interest in regenerative medicine. Over the last 10 years, detailed studies investigated the properties of MSC from perinatal tissues and have indicated that these cells may represent important tools for restoring tissue damage or promoting regeneration and repair of the tissue microenvironment. At first, perinatal tissue-derived MSC drew attention due to their potential differentiation capacities suggested by their early embryological origin. It is nowadays accepted that perinatal tissue-derived MSC are promising for a wide range of regenerative medicine applications because of their unique immune modulatory properties, rather than their differentiation ability. As a matter of fact, the activation and function of various cells of the innate and adaptive immune systems are suppressed and modulated by MSC from different perinatal tissues, such as human term placenta. However, the mechanisms by which they act on immune cells to facilitate tissue repair during pathological processes remain to be thoroughly elucidated to develop safe and efficient therapeutic approaches. In addition to immune modulatory ability, several other peculiar characteristics of placenta MSC, less explored and/or more debated, are being investigated. These include an understanding of the anti-microbial properties and the role of placental MSC in tumor progression. Moreover, a thorough investigation on preparation methods, bioactive factors, mechanisms of action of the cell secretome, and the development of potency assays to predict clinical efficacy of placenta MSC and their products, are necessary to provide a solid basis for their clinical application.